The Porcine Antibody Repertoire: Variations on the Textbook Theme - Butler, John (Frontiers in Immunology, 2012)
The genes encoding the heavy and light chains of swine antibodies are organized in the same manner as in other eutherian mammals. There are 30 VH genes, two functional DH genes and one functional JH gene. There are 14-60 V genes and 5 J segments, >22V genes and at least four JC cassettes. The heavy chain constant regions encode the same repertoire of isotypes common to other eutherian mammals. The piglet models offers advantage over rodent models since the fetal repertoire develops without maternal influences and the precocial nature of their multiple offspring allows the experimenter to control the influences of environmental and maternal factors on repertoire development postnatally. B cell lymphogenesis in swine begins in the fetal yolk sac at 20 days of gestation (DG), moves to the fetal liver at 30 DG and eventually to the bone marrow which dominates until birth (114 DG) and to at least 5 weeks postpartum. There is no evidence that the ileal Peyers patches are a site of B cell lymphogenesis or are required for B cell maintenance. Unlike rodents and humans, light chain rearrangement begins first in the lambda locus; kappa rearrangements are not seen until late gestation. Dissimilar to lab rodents and more in the direction of the rabbit, swine utilize a small number of VH genes to form >90% of their pre-immune repertoire. Diversification in response to environmental antigen does not alter this pattern and is achieved by somatic hypermutation (SHM) of the same small number of VH genes. The situation for light chains is less-well studied, but certain V and J and V and J are dominant in transcripts. The transcribed and secreted pre-immune antibodies of the fetus include mainly IgM, IgA and IgG3; this last isotype may provide a type of first responder mucosal immunity. Development of functional adaptive immunity is dependent on bacterial PAMPs or PAMPs provided by viral infections, indicating the importance of innate immunity for development of adaptive